ByzRev 07.2025.016: Roland Betancourt, The Secrets We Keep: Hidden Histories of the Byzantine Empire.: Los Angeles: Getty Research Institute 2024. - Anderson, Benjamin (The Byzantine Review, 2025)
Roland Betancourt, The Secrets We Keep: Hidden Histories of the Byzantine Empire. Los Angeles: Getty Research Institute 2024. 90 pp., 23 ill., incl. 1 map. – ISBN 978-1-60606-908-0